Effects of saponins Rb1 and Re in American ginseng intervention on intestinal microbiota of aging model - Shi, Mao; Fan, HongXiu; Liu, HongCheng; Zhang, YanRong (Frontiers in Nutrition, 2024)
Aging brings about physiological dysfunction, disease, and eventual mortality. An increasing number of studies indicate that aging can easily lead to dysbiosis of the gut microbiota, which can further affect digestion, nerves, cognition, emotions, and more. Therefore, gut bacteria play an important role in regulating the physical functions of aging populations.While saponins, the primary components of American ginseng, are frequently utilized for treating common ailments in the elderly due to their potent antioxidant properties, there is a scarcity of comprehensive studies on aging organisms.This study focused on 18 month old aging mice and investigated the effects of single intervention and combined intervention of Rb1 and Re, the main components of Panax quinquefolium saponins, on the gut microbiota of aging mice.High throughput 16s RNA gene sequencing analysis was performed on the gut contents of the tested mice, and the results showed that Rb1 and Re had a significant impact on the gut microbiota. Rb1, Re, and Rb1+Re can effectively enhance the diversity of gut microbiota, especially in the combined Rb1+Re group, which can recover to the level of young mice. Re can promote the abundance of probiotics such as Lactobacillus, Lactobacillaceae, and Lactobacillus, and inhibit the abundance of harmful bacteria such as Enterobacteriaceae. This indicates that the intervention of Rb1, Re, and Rb1+Re can maintain the homeostasis of gut microbiota, and the combined application of Rb1+Re has a better effect.The relationship between aging, brain gut axis, and gut microbiota is very close. Saponins can improve the gut microbiota of aging individuals by maintaining the balance of gut microbiota and the normal function of the brain gut axis, enabling the body to achieve a gut microbiota homeostasis closer to that of young healthy mice.